Analysis of the use of long term contraceptive methods - Wahyuni, Sri; Latif, Farida (Jurnal Ilmiah Kesehatan Sandi Husada, 2025)
Introduction: Indonesia ranked third among ASEAN countries in maternal mortality rate (MMR) in 2017, with 177 deaths per 100,000 live births. This high rate has prompted various governmental initiatives to reduce MMR, with the family planning (FP) program being one of the most effective strategies. However, the uptake of long-acting and permanent contraceptive methods (LAPMs) remains low, particularly due to social and personal barriers. This study aims to analyse the factors influencing the use of long-acting contraceptive methods (LAPMs) among family planning acceptors. Method: A quantitative correlational study with a cross-sectional design was employed. The study involved 35 FP acceptors selected from a population 62 using accidental sampling. Data were collected using a structured questionnaire and analysed through the Chi-square test with a significance threshold of α = 0.05. Results: The findings revealed significant associations between LAPM use and three key factors: knowledge (p = 0.036), attitude (p = 0.027), and husband’s support (p = 0.005). Most respondents who did not use LAPMs had poor knowledge, unfavourable attitudes, and lacked spousal support. Conclusion: There is a statistically significant relationship between knowledge, attitude, husband’s support and the use of long-acting contraceptive methods. These findings highlight the importance of educational interventions and partner involvement in enhancing LAPM uptake